Fish fauna of Baía da Babitonga (southern Brazil), with remarks on species abundance, ontogenic stage and conservation status - Vilar, Ciro Colodetti; Spach, Henry Louis; Santos, Lilyane De Oliveira (Zootaxa, 2011)
Basic data on species composition and abundance are essential to subsidize the development of effective actions for conservation of biological diversity and to identifying the effects arising from these actions. This work provides an updated checklist of the fish species occurring in the proposed Baía da Babitonga marine protected area (southern Brazil) as well as their abundance, ontogenic stage and conservation status, based on multi-site data collected in shallow water and deeper zones of the main channel and from published literature. A total of 152 fish species belonging to 18 orders and 53 families were registered, with 29 species being reported for the first time in Baía da Babitonga. Among the registered species, the exotic blenny Omobranchus punctatus (Valenciennes) was the most unexpected. The most species-rich families were Sciaenidae (18), Carangidae (15), Engraulidae (9), Paralichthyidae (8), Epinephelidae (8) and Gobiidae (7). Nine species inhabiting Baía da Babitonga are classified as globally threatened, and 17 species are classified as nationally overexploited; four of these species are on both global and national red lists.